ANALYSIS OF SCIENCE PROCESS SKILLS AMONG ELEMENTARY SCHOOL STUDENTS - Sutisnawati, Astri; Rahmawati, Yuli; Sumantri, M. Syarif (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Elementary school students frequently face difficulties in grasping abstract science concepts, often exhibiting limited foundational scientific skills. Additionally, they tend to experience a teacher-centered approach to science instruction, which may impede their engagement and understanding. This study aims to investigate the science process skills of fifth-grade students as they explore the topic of light and its various properties. Conducted across three different schools, the research involved a total of 90 fifth-grade students. A qualitative methodology was employed to gain insights into the development of their science process skills during the learning experience. Data collection included assessments of science process skills as well as detailed observation sheets to monitor student engagement and performance. The findings indicated that students' performance on the science process skills tests fell within a moderate range. They encountered the most challenges in planning and conducting investigations, vital components of scientific inquiry. In contrast, they demonstrated greater proficiency in observational activities, suggesting that they possess the ability to make careful observations—an essential foundational skill in science education. This study highlights areas for improvement and underscores the importance of fostering a more hands-on and exploratory approach to teaching science.